Powder rubber with lithium stearate and use thereof as electrode binder
By using powdered rubber prepared by lithium stearate as a binder, combined with ethylene-vinyl acetate or nitrile rubber copolymer, the problem of insufficient flexibility and adhesion of the cathode material of lithium ion battery is solved, and the cathode plate is improved Performance and security.
Patent Information
- Application Number
- CN202380043110.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art lacks suitable powdered polymer binders suitable for cathode active materials for lithium ion batteries, and traditional fluorinated polymer binders such as PVDF have insufficient flexibility and adhesion, which can easily lead to cathode material. Expansion and cracks, and risks of fire and toxic gas release.
Lithium stearate is used as a dustproof agent to prepare free-flowing powdered rubber, which is used as a new binder, combined with ethylene-vinyl acetate copolymer or nitrile rubber copolymer to form a high adhesion and flexible electrode composition. , an electrode composition for cathode of lithium ion battery.
It improves the peel strength and capacity retention rate of the cathode plate, reduces fire risk and toxic gas release, and provides better electrochemical stability and processing performance.
Smart Images

Figure BDA0005154501840000141 
Figure BDA0005154501840000151 
Figure BDA0005154501840000161
Abstract
Description
[0001] The present invention generally relates to a binder for an electrode composition of a battery cell cathode for a lithium ion battery, a cathode slurry composition comprising the electrode composition, a cathode, a method for making the cathode, and a lithium ion battery having one or more battery cells incorporating the cathode. In particular, the present invention relates to powdered rubber having a lithium salt as a dust suppressant and its use as a binder in battery applications. Technical Field
[0002] Lithium-ion batteries consist of at least two electrically conductive Coulombic electrodes of different polarity: a negative electrode or anode (usually made of graphite) and a positive electrode or cathode, with a separator located between the two electrodes. + The cathode of a lithium-ion battery is composed of an electrical insulator impregnated with a non-protonic electrolyte of ionic cations, thereby ensuring ionic conductivity. The electrolyte used in these lithium-ion batteries is typically composed of a lithium salt such as LiPF6, LiAsF6, LiCF3SO3 or LiCO4, which is dissolved in a mixture of non-aqueous solvents such as acetonitrile, tetrahydrofuran or more common carbonates (such as ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, vinylene carbonate or propylene carbonate). The active material of the cathode of a lithium-ion battery allows lithium ions to be reversibly inserted into / removed from this cathode, and the higher the mass fraction of this active material in the cathode, the higher its capacity. The cathode must also contain a conductive compound such as carbon black and in order to provide it with sufficient mechanical cohesion, it must also contain a polymer binder, which is also required for good adhesion to the current collecting foil. Therefore, the binder must interact with both the active material and the conductor while maintaining electrochemical stability and high flexibility. Lithium-ion batteries are therefore based on the reversible exchange of lithium ions between an anode and a cathode during charging and discharging of the battery and have a high energy density for a very low weight due to the physical properties of lithium.
[0003] The cathode of a lithium-ion battery is generally manufactured using a method comprising, in sequence, a step of dissolving and / or dispersing a polymer binder, an active material, a conductive material and optionally a dispersant in a solvent, a step of applying the obtained cathode slurry composition to a current collector, and then finally a step of evaporating the solvent.
[0004] The polymer binder is dispersed in the cathode slurry composition to improve the adhesion between the cathode active materials and the adhesion between the cathode active materials and the current collector. At the same time, the polymer binder helps to disperse the conductive material. The electrolyte retention ability of the polymer binder improves the battery characteristics.
[0005] During the charge-discharge process, lithium ions are loaded and unloaded into the active material. Due to this movement of lithium ions, expansion and dilation of the cathode and anode materials may occur. Therefore, for lithium-ion batteries, it is very desirable to use elastic materials as binders to allow the active materials to move flexibly during use without delamination or cracking from the current collector. Unfortunately, highly crystalline binders may be too hard to move, and rubber-type binders would be preferred.
[0006] Polymer binders are an important part of the electrode and are used to help disperse the active materials and conductive materials in the cathode slurry composition, to stabilize these materials in the slurry during cathode preparation, and to enable a smooth cathode with a well-defined pore structure. During use, the cohesion of the cathode and its adhesion to the current collector are crucial and are strongly affected by the type of binder used and the corresponding functional part of its polymer. Adhesion and cohesion are key properties of polymer binders, which determine the final performance of lithium-ion batteries, especially the long-term performance. Good polymer binders ensure uniform dispersion of active materials and conductive materials and stable bonding with the metal current collector.
[0007] Many types of polymer binders can be used, however, there is a gradual shift away from conventional electrodes using fluorinated polymers based on PVDF (polyvinylidene fluoride) or mixtures of PVDF with various other polymer binders such as carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), hydrogenated nitrile rubber (HNBR) or polyacrylic acid (PAA), which are readily compatible with cathodes operating at high operating voltages and available in powder form. PVDF is the most widely used polymer binder in lithium-ion batteries because it exhibits electrochemical stability, bonding strength and low thermal degradation. Due to its high level of crystallinity, PVDF provides high resistance in typical electrolytes used in lithium-ion batteries. However, the low flexibility of PVDF may not meet the requirements for the cathode because the bond between the cathode active material and the conductive material breaks when a flexible electrode is required, or when the negative active material undergoes a persistent expansion / contraction process during cycling, and when higher adhesion is required to reduce the total binder amount in the cathode. Other non-fluorinated polymer binders such as HNBR are not yet available in any powder form, which does not facilitate easier processing of the battery.
[0008] Additionally, occasional battery fires have raised some concerns, particularly regarding the risk of spontaneous fires and the high heat generated by such fires. While the fire itself and the heat it generates can be a serious threat in many situations, the risks associated with the emission of gases and smoke produced by malfunctioning lithium-ion batteries can be a greater threat in some cases, particularly in confined environments with people present, such as in aircraft, submarines, mines, spacecraft, or homes equipped with battery energy storage systems. At high temperatures, battery components, such as the polyvinylidene fluoride (PVDF) binder in the electrodes, can form toxic gases such as hydrogen fluoride (HF).
[0009] Many studies have also focused on the optimization of cathode active materials to improve the electrochemical properties of lithium-ion batteries, while in the past, less attention has been paid to the research progress of non-electroactive components of the cathode, such as polymer binders. However, the recent trend is to develop new electrode compositions based on typical cathode active materials to replace fluoropolymer binders such as PVDF with polymer binders with good adhesion and cohesion and high capacity retention to obtain long-life batteries.
[0010] EP 3 283 538 relates to a powdery mixture containing at least one acrylonitrile-butadiene rubber and at least one separating agent, and these powdery mixtures are characterized in that the mean particle size specified.Described mixture has a particularly low emission level and is extremely suitable for producing materials and components for indoor applications.The powdery mixture with low emission level is obtained by using a specific molecular weight modifier.In this invention, different dust suppressants have been summed up, yet, no mention is made of any lithium salt-containing purposes, nor is the purposes of powdered rubber in any battery application mentioned.
[0011] EP 3 902 855 relates to a powdered mixture based on special pre-crosslinked paracril and at least a releasing agent, further relates to a method for producing vulcanizable mixture and vulcanized rubber from these powdered mixtures and these vulcanized rubbers obtained and purposes thereof, especially in tire tread.By using a specific trifunctional acrylate crosslinking agent in the polymerization of paracril, standard dust-proofing agents such as silicon dioxide or Ca salt can be used to prepare powdered rubber from those paracril.When using those powdered paracril as the additive in the tire tread, the wet grip of tire can be improved.In this invention, different dust-proofing agents have been summed up, no mention of any purposes containing lithium salts, no mention of the purposes of those powdered rubbers in any battery application.
[0012] EP 3 900 086 relates to an electrode composition for a cathode of a battery cell of a lithium ion battery, the electrode composition comprising a fluorine-free copolymer containing epoxy groups; a cathode slurry composition comprising the electrode composition; a cathode; a method for manufacturing the cathode; and a lithium ion battery having one or more battery cells incorporating the cathode. The fluorine-free copolymers containing epoxy groups are NBR or EVM polymers. There is no description of converting those rubbers into powders, or the use of the powdered rubbers in battery applications.
[0013] However, suitable powdered polymer binders for Li-containing cathode active materials have not been found to date to provide electrode compositions for battery cell cathodes of lithium-ion batteries that are suitable for battery applications and also show improvements over standard PVDF binders.
[0014] It is therefore an object of the present invention to provide an electrode composition for a cathode of a lithium ion battery which overcomes some or all of the above-mentioned disadvantages.
[0015] It is an object of the present invention to provide an electrode composition that can be used to provide a cathode having improved properties compared to cathodes comprising a standard PVDF binder.
[0016] Surprisingly, lithium stearate was found to act as a dust suppressant for elastomers, resulting in free-flowing powdered rubbers that also exhibited good electrode processing properties and rapid solubility in typical battery solvents. Furthermore, the dust suppressant used can act as a sacrificial anode, resulting in improved battery performance.
[0017] By screening and evaluating different dust suppressants and their use in preparing powdered polymer binders, surprisingly, lithium salts are identified as new dust suppressants for battery applications. By using those lithium salts as new dust suppressants, free-flowing polymer powders can be obtained, and in battery application tests, different polymer powders all maintain higher adhesion of cathode plates compared with standard PVDF binders. In addition, relative to non-inventive polymer powders or even non-powdered rubber samples, discharge specific capacity decay is improved. It is assumed that the added lithium salt can be used as a sacrificial anode in a battery, thereby resulting in better capacity retention. Summary of the invention
[0018] The object of the present invention has been achieved by providing an elastomer powder mixture comprising
[0019] (1) (a) Ethylene-vinyl acetate copolymer (EVA) containing the following repeating units:
[0020] - ethylene monomer, and
[0021] - vinyl acetate monomer in an amount of at least 70% by weight and based on the total weight of the ethylene-vinyl acetate copolymer;
[0022] or
[0023] (b) nitrile rubber copolymers (NBR), which are optionally carboxylated (XNBR) and contain the following repeating units:
[0024] - α,β-unsaturated nitrile monomers selected from the group consisting of acrylonitrile, methacrylonitrile, ethacrylonitrile and mixtures thereof, preferably in an amount of at least 15% by weight in each case and based on the total weight of the nitrile rubber copolymer, and
[0025] - a conjugated diene monomer, which is optionally fully or partially hydrogenated (HNBR) and is selected from the group consisting of 1,2-butadiene, 1,3-butadiene, isoprene, 2,3-dimethylbutadiene, piperylene and mixtures thereof;
[0026] as well as
[0027] (2) A dust suppressant comprising lithium stearate.
[0028] In the context of the present invention, the terms "pulverulent" and "powderous", preferably "free-flowing powderous", may be used synonymously.
[0029] In the context of the present invention, the terms "antidust agent" and "separating agent" can be used synonymously and refer to pulverulent mixtures in order to avoid agglomeration of the individual elastomer particles.
[0030] Preferably, the pulverulent mixture has a particle size distribution D90 of at least 100 μm, more preferably of 200 μm to 750 μm, as determined by using a laser diffuser and using the Fraunhofer approximation.
[0031] Preferably, the powdered mixture is fluorine-free.
[0032] Preferably, the nitrile rubber copolymer (b) is a carboxylated nitrile rubber (XNBR).
[0033] Preferably, the ethylene vinyl acetate copolymer (a) or the nitrile rubber copolymer (b) has a Mooney viscosity (ML (1+4) 100°C) of ≥ 25 Mooney units (MU), more preferably of 28 to 120 Mooney units (MU), measured at 100°C by shear disc viscometer according to DIN 53523 / 3 or ASTM D 1646.
[0034] Preferably, lithium stearate is present in an amount of at least 3% by weight, more preferably 3% by weight to 60% by weight, still more preferably 5% by weight to 40% by weight, yet more preferably 5% by weight to 20% by weight, in each case based on the total weight of the powdered mixture.
[0035] Preferably, lithium stearate is used as the dust suppressant.
[0036] Preferably, the powdered mixture contains no anti-dust agents other than lithium stearate.
[0037] In another preferred embodiment, however, the pulverulent mixture contains at least one dust suppressant in addition to lithium stearate.
[0038] Suitable copolymers and lithium stearate are available to the skilled person. For example, suitable copolymers are provided under the following trade names: 900, XT, AT LT2004VP, LT1707VP, 3407, M20VP, 4307, 3945, M20VP and X 146. Likewise, methods for producing and determining suitable copolymers are available to the skilled person (see for example EP 3 283 538, EP 3 902 855 and EP 3 900 086).
[0039] The term "copolymer" encompasses polymers having more than one monomer unit. In one embodiment of the invention, the respective copolymer is derived only from monomer types such as those described above. The term "copolymer" also additionally encompasses terpolymers or tetrapolymers such as those derived from monomer types such as those described above and at least one further monomer unit.
[0040] These monomers are preferably distributed statistically over the polymer chain of the copolymers used according to the invention.
[0041] The fully hydrogenated nitrile rubber copolymer (b) preferably contains less than 1% of the residual double bonds of the fully unsaturated copolymer (b).The partially hydrogenated nitrile rubber copolymer (b) preferably contains 1% or more of the residual double bonds of the fully unsaturated copolymer (b).
[0042] In a second aspect, the present invention relates to a cathode slurry composition comprising a powdered mixture according to the present invention, at least one cathode active material, at least one conductive material, and at least one solvent.
[0043] In a third aspect, the present invention relates to a cathode comprising a current collector and a cathode active material layer, wherein the cathode active material layer comprises the powdered mixture according to the present invention and a conductive material.
[0044] In a fourth aspect, the invention relates to a lithium-ion battery comprising at least one battery cell comprising an anode, a cathode according to the invention, a separator and an electrolytic solution based on a lithium salt and an organic solvent.
[0045] Preferably, the cathode plate of the lithium ion battery has a peel strength of at least 340 N / m, which is preferably measured according to the experimental part of the present application.
[0046] In a fifth aspect, the invention relates to the use of the pulverulent mixture according to the invention as a binder in an electrode composition for a cathode of a battery cell of a battery. DETAILED DESCRIPTION
[0047] Additional monomer units
[0048] Copolymers (a), (b) and (c) may contain at least one additional monomer unit in addition to the monomer units described above. Exemplary additional monomer units are defined below.
[0049] Preferred examples of the additional epoxy-containing monomer are selected from the group consisting of 2-ethyl glycidyl acrylate, 2-ethyl glycidyl methacrylate, 2-(n-propyl) glycidyl acrylate, 2-(n-propyl) glycidyl methacrylate, 2-(n-butyl) glycidyl acrylate, 2-(n-butyl) glycidyl methacrylate, glycidyl methyl acrylate, glycidyl methyl methacrylate, glycidyl acrylate, glycidyl methacrylate, (3′,4′-epoxyheptyl)-2-ethyl acrylate , (3′,4′-epoxyheptyl)-2-ethyl methacrylate, 6′,7′-epoxyheptyl acrylate, 6′,7′-epoxyheptyl methacrylate, allyl glycidyl ether, allyl 3,4-epoxyheptyl ether, 6,7-epoxyheptyl allyl ether, vinyl glycidyl ether, vinyl 3,4-epoxyheptyl ether, 3,4-epoxyheptyl vinyl ether, 6,7-epoxyheptyl vinyl ether, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether and 3-vinylcyclohexene oxide.
[0050] Most preferably, the epoxy-containing monomer is a glycidyl (alkyl)acrylate, preferably glycidyl acrylate and / or glycidyl methacrylate.
[0051] Furthermore, the copolymer used according to the present invention may additionally contain repeating units of one or more additional copolymerizable monomers known in the art, such as α,β-unsaturated (preferably monounsaturated) monocarboxylic acids, their esters and amides, α,β-unsaturated (preferably monounsaturated) dicarboxylic acids, their monoesters or diesters, and the corresponding anhydrides or amides of the α,β-unsaturated dicarboxylic acids, vinyl esters, vinyl ketones, vinyl aromatic compounds, α-monoolefins, vinyl monomers having hydroxyl groups and carbon monoxide.
[0052] As α,β-unsaturated monocarboxylic acids, preference is given to using acrylic acid and methacrylic acid.
[0053] Esters of α,β-unsaturated monocarboxylic acids, preferably alkyl esters and alkoxyalkyl esters thereof, may also be used. Alkyl esters of α,β-unsaturated monocarboxylic acids, especially C1-C 18 -alkyl esters. Particularly preferred are alkyl esters of acrylic acid or methacrylic acid, especially C1-C 18 -alkyl esters, in particular methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, n-dodecyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate and 2-ethylhexyl methacrylate. Preference is also given to alkoxyalkyl esters of α,β-unsaturated monocarboxylic acids, particularly preferably alkoxyalkyl esters of acrylic acid or methacrylic acid, in particular C2-C 2-unsaturated monocarboxylic acids of acrylic acid or methacrylic acid. 14 - alkoxyalkyl esters, very particularly preferably methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate and methoxyethoxyethyl (meth)acrylate; butoxydiethylene glycol methacrylate, polyethylene glycol acrylate and polyethylene glycol methacrylate. It is also possible to use mixtures of alkyl esters such as those mentioned above with alkoxyalkyl esters, for example in the form of those mentioned above. It is also possible to use hydroxyalkyl acrylates and hydroxyalkyl methacrylates, in which the number of carbon atoms in the hydroxyalkyl group is 1 to 12; preferably 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate and 3-hydroxypropyl acrylate; it is also possible to use α,β-unsaturated carboxylic acid esters containing amino groups, for example dimethylaminomethyl acrylate, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxymethyl)acrylamide, (meth)acrylic acid carbamate and diethylaminoethyl acrylate.
[0054] It is also possible to use α,β-unsaturated dicarboxylic acids, preferably maleic acid, fumaric acid, crotonic acid, itaconic acid, citraconic acid and mesaconic acid, as further copolymerizable monomers.
[0055] It is also possible to use α,β-unsaturated dicarboxylic anhydrides, preferably maleic anhydride, itaconic anhydride, citraconic anhydride and mesaconic anhydride.
[0056] Monoesters or diesters of α,β-unsaturated dicarboxylic acids may also be used. These α,β-unsaturated dicarboxylic acid monoesters or diesters may be, for example, alkyl (preferably C1-C 10 -alkyl, in particular ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl or n-hexyl) monoesters or diesters, alkoxyalkyl (preferably C2-C 12 -alkoxyalkyl, particularly preferably C3-C8-alkoxyalkyl) monoesters or diesters, hydroxyalkyl (preferably C1-C 12 -hydroxyalkyl, particularly preferably C3-C8-hydroxyalkyl) monoesters or diesters, cycloalkyl (preferably C5-C 12 -cycloalkyl, particularly preferably C6-C 12 -cycloalkyl) monoester or diester, alkylcycloalkyl (preferably C6-C 12 -alkylcycloalkyl, particularly preferably C7-C 10 -alkylcycloalkyl) monoester or diester, aryl (preferably C6-C 14 -aryl) monoesters or diesters, where the diesters can in each case also be mixed esters.
[0057] As α,β-unsaturated dicarboxylic acid diesters it is possible to use analogous diesters based on the abovementioned monoester radicals, where the ester radical can also be chemically different ester radicals.
[0058] As the vinyl ester, for example, vinyl propionate and vinyl butyrate can be used.
[0059] As the vinyl ketone, for example, methyl vinyl ketone and ethyl vinyl ketone can be used.
[0060] As the vinyl aromatic compound, for example, styrene, α-methylstyrene and vinyltoluene can be used.
[0061] As α-monoolefins, for example, C2-C 12 - Olefins, for example propylene, 1-butene, 4-butene, 4-methyl-1-pentene, 1-hexene and 1-octene.
[0062] Possible additional copolymerizable monomers are also free-radically polymerizable compounds containing at least two olefinic double bonds per molecule. Such monomers thus lead to a certain degree of precrosslinking of the copolymers (a), (b) or (c). Examples of polyunsaturated compounds are acrylates, methacrylates or itaconates of polyols, for example ethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol diacrylate, 1,4-butylene glycol diacrylate, 1,2-propylene glycol diacrylate, 1,3-butylene glycol dimethacrylate, neopentyl glycol diacrylate, trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol diacrylate and triacrylate. Esters, di-, tri- and tetra-acrylates or di-, tri- and tetra-methacrylates of pentaerythritol, dipentaerythritol tetra-, penta- and hexa-acrylates or tetra-, penta- and hexa-methacrylates or tetra-, penta- and hexa-itaconates of dipentaerythritol, tetra-, penta- and hexa-acrylates or tetra-, penta- and hexa-methacrylates of dipentaerythritol, tetra-, penta- and hexa-itaconates of sorbitol tetraacrylate, sorbitol hexamethacrylate, diacrylates or dimethacrylates of 1,4-cyclohexanediol, 1,4-dihydroxymethylcyclohexane, 2,2-bis(4-hydroxyphenyl)propane; acrylates, methacrylates or itaconates of oligoesters or urethanes of polyethylene glycol or oligomeric esters with terminal hydroxyl groups. As polyunsaturated monomers, acrylamides such as methylenebisacrylamide, hexamethylene-1,6-bisacrylamide, diethylenetriaminetrimethylacrylamide, bis(methacrylamidopropoxy)ethane or 2-acrylamidoethyl acrylate can also be used. Examples of polyunsaturated vinyl and allyl compounds are divinylbenzene, ethylene glycol divinyl ether, diallyl phthalate, allyl methacrylate, diallyl maleate, triallyl isocyanurate or triallyl phosphate.
[0063] Acetoacetoxyethyl methacrylate is another example of a preferred additional monomer.
[0064] The total proportion of further copolymerizable monomers incorporated is less than 35% by weight, preferably less than 25% by weight, particularly preferably less than 20% by weight, and especially preferably less than 15% by weight, based on copolymer (a), (b) or (c). The total content of the above-mentioned monomers and these optionally used further monomers adds up to 100% by weight, based on copolymer (a), (b) or (c).
[0065] Cathode active material
[0066] The cathode active material according to the present invention is preferably selected from the following group: lithium-containing metal oxides that accept and provide electrons in the cathode, including optionally layered lithium-containing metal oxides such as LiCoO2, LiNiO2, LiMn2O4 or LiNiMnCoO2; lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2, etc.; lithium nickel manganese cobalt oxides such as Liw Ni x Mn y Co z O2, etc.; lithium nickel cobalt aluminum oxides, such as LiNiCoAlO2, etc.; or even modified nickel manganese cobalt oxides, such as Li 1+a Ni x Mn z Co y M w O2, where M can be at least one selected from the group consisting of aluminum (Al), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), tantalum (Ta), niobium (Nb), magnesium (Mg), boron (B), tungsten (W), and molybdenum (Mo), and a, x, y, z, and w represent the atomic fractions of each independent element, where -0.5 ≤ a ≤ 0.5, 0 < x ≤ 1, 0 < y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ w ≤ 1, and 0 < x + y + z ≤ 1; lithium titanate, such as Li4Ti5O 12 etc.; lithium copper oxide, such as Li2CuO2; vanadium oxide, such as LiV3O8; LiFe3O4; or phosphate, such as LiCoPO4 or LiFePO4.
[0067] In a preferred embodiment, the at least one cathode active material comprises a compound having Formula 1:
[0068] Li 1+a Ni x Co y Mn z M w O2 [Formula 1]
[0069] wherein, M can be at least one selected from the group consisting of aluminum (Al), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), tantalum (Ta), niobium (Nb), magnesium (Mg), boron (B), tungsten (W), and molybdenum (Mo), and a, x, y, z, and w represent the atomic fractions of each independent element, where -0.5 ≤ a ≤ 0.5, 0 < x ≤ 1, 0 < y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ w ≤ 1, and 0 < x + y + z ≤ 1; or lithium iron phosphate (LFP).
[0070] In another preferred embodiment, the cathode active material may include a nickel-excess lithium composite metal oxide, where -0.5 ≤ a ≤ 0.5, 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 ≤ w ≤ 1, and y + z ≤ x in Formula 1.
[0071] In another preferred embodiment, the cathode active material may include LiNi 0.3 Mn 0.3 Co0.3 O2、LiNi 0.6 Mn 0.2 Co 0.2 O2、LiNi 0.5 Mn 0.3 CO 0.2 O2、LiNi 0.7 Mn 0.15 CO 0.15 O2 or LiNi 0.8 Mn 0.1 Co 0.1 O2, and any one of them or a mixture of two or more thereof may be used.
[0072] Particularly preferred cathode active materials according to the invention are lithium nickel cobalt manganese oxide (NMC), lithium iron phosphate (LFP) or lithium nickel cobalt aluminum oxide (NCA). Particularly preferred is lithium nickel cobalt manganese oxide (NMC).
[0073] Conductive Materials
[0074] The cathode slurry composition contains at least one electrically conductive material (hereinafter referred to as "conductive material"). Preferred conductive materials are selected from the group consisting of carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and summer black, natural and artificial graphite, expanded graphite, conductive fibers such as carbon fibers and metal fibers, metal powders such as fluorinated carbon, aluminum powder and nickel powder, as well as carbon nanotubes, graphene, graphene oxide, and mixtures thereof. By including the conductive material, the electrical connection of the cathode active material can be improved, and the discharge rate characteristics can be improved.
[0075] In a preferred embodiment, the conductive material is present in the cathode slurry composition in an amount of 0.5% to 50% by weight based on the total solids weight of the cathode slurry composition.
[0076] Solvents
[0077] The cathode slurry composition includes at least one solvent. As long as the binder according to the present invention can be uniformly (partially) dispersed or dissolved, the solvent is not particularly limited, and water or an organic solvent may be used. The organic solvent may include cyclic aliphatic hydrocarbons such as cyclopentane and cyclohexane; aromatic hydrocarbons such as chlorobenzene, toluene, xylene and cyclobenzene; ketones such as acetone, methyl ethyl ketone, diisopropyl ketone, cyclohexanone, methylcyclohexane, ethylcyclohexane; chlorinated aliphatic hydrocarbons such as dichloromethane, chloroform and carbon tetrachloride; esters such as ethyl acetate, butyl acetate, γ-butyrolactone, ε-caprolactone; acrylonitrile such as acetonitrile or propionitrile; ethers such as tetrahydrofuran or ethylene glycol diethyl ether; alcohols such as tert-butyl alcohol, glycerol, methanol, ethanol, isopropanol, ethylene glycol, triethylene glycol or ethylene glycol monomethyl ether; sulfones such as diethyl sulfone, ethyl methyl sulfone or tetramethylene sulfone, nitriles such as malononitrile or succinonitrile, amides such as N-methylpyrrolidone (NMP), N-formylmorpholine and N,N-dimethylformamide may be mentioned. Preferred solvents are methyl ethyl ketone, toluene and N-methylpyrrolidone. Particularly preferred is N-methylpyrrolidone.
[0078] Method for producing cathode slurry composition
[0079] The production method of the cathode slurry composition used in the present invention is not particularly limited, and is produced by mixing the binder according to the present invention with the cathode active material, the conductive material and optionally another additive. Alternatively, but not limited to, before adding a solvent, the binder according to the present invention is first mixed with the cathode active material, the conductive material and optionally another additive.
[0080] As long as the binder solution, cathode active material and conductive material can be uniformly mixed, the mixing device is not particularly limited; and for example, a method using a mixing device such as a stirring type, a shaking type and a rotating type can be mentioned. In addition, a method using a dispersing kneader (such as a homogenizer, a ball mill, a sand mill, a roller mill), a planetary kneader (such as a planetary mixer) or an extruder can also be mentioned.
[0081] Cathode (positive electrode)
[0082] The cathode of the secondary battery of the present invention comprises a current collector and a cathode active material layer. The cathode active material layer comprises the electrode composition of the present invention, a conductive material, and may also comprise other optional components added as required. The cathode active material layer is formed on the current collector.
[0083] current collector
[0084] If the current collector is a material with electrical conductivity and electrochemical durability, it is not particularly limited. Preferably, in view of heat resistance, the current collector is selected from the group consisting of: iron, copper, aluminum, nickel, sintered carbon, stainless steel, stainless steel treated with carbon, titanium, tantalum, gold, platinum, titanium or silver on its surface; aluminum-cadmium alloy, non-conductive polymer treated with conductive material on its surface; conductive polymer or metal paste containing metal powder of Ni, Al, Au, Ag, Pd, Cr, Ta, Cu or Ba. Among these, aluminum is particularly preferred as the current collector of the cathode. The current collector can be formed in various forms, such as in the form of a film, a plate, a foil, a mesh, a porous body, a foam or a non-woven fabric. The shape of the current collector is not particularly limited, and preferably has a plate-form current collector with a thickness of about 0.001 to 0.5 mm, more preferably 3 to 500 μm. Preferably, in order to improve the adhesion strength with the cathode active material layer, the current collector is roughened in advance before use. The method of roughening treatment may include mechanical polishing, electropolishing, chemical polishing, etc. When mechanically polishing the cathode, a coated abrasive cathode, a grinding stone, a diamond polishing agent or a wire brush provided with a steel wire fixed with abrasive particles can be used. In addition, an intermediate or primer coating can be formed on the surface of the current collector to increase the adhesion strength and conductivity between the cathode active material layer and the current collector.
[0085] Method for manufacturing a cathode
[0086] The invention further relates to a method for producing a cathode as defined above, characterised in that the method comprises the following steps:
[0087] (1) dissolving a binder according to the present invention in a solvent to form a binder solution; and
[0088] (2) mixing the binder solution from step (1) with a cathode active material, a conductive material, and optionally additional additives to form a cathode slurry composition;
[0089] (3) applying the cathode slurry composition from step (2) to a current collector to form a cathode plate; and
[0090] (4) Drying the cathode plate of step (3).
[0091] In an alternative embodiment, before adding the solvent, the binder according to the invention, the cathode active material, the conductive material and optionally the further additives of steps (1) and (2) are first mixed. In a preferred embodiment, the binder according to the invention is first dissolved in the solvent according to step (1).
[0092] In a preferred embodiment of the present invention, but not limited to, step (1) can be carried out by dissolving the binder according to the present invention in an oscillator at room temperature overnight. In a preferred embodiment of the present invention, the binder solution formed in step (1) has a concentration of 0.1% to 30% by weight, preferably 0.25% to 20% by weight, and more preferably 0.5% to 15% by weight based on the total weight of the binder solution.
[0093] In a preferred embodiment of the present invention, but not limited to, step (2) can be carried out in a ball mill (including a dry ball mill, a wet ball mill, a planetary ball mill) or a rotary drum mixer.
[0094] In a preferred embodiment of the present invention, but not limited thereto, step (3) may be performed using a bar coater or a doctor blade, more preferably a bar coater with a slit gap of 50 to 750 μm.
[0095] In a preferred embodiment of the present invention, step (4) may be performed in an oven, more preferably at a temperature of 50°C to 200°C, even more preferably at a temperature of 50°C to 150°C.
[0096] In a preferred embodiment, but not limited to, the cathode plate is calendered after the drying step (4) to adjust the area density.
[0097] The cathode is punched out from the calendered cathode sheet.
[0098] Lithium-ion battery
[0099] The invention further relates to a lithium ion battery comprising one or more battery cells comprising the cathode of the invention. The lithium ion battery according to the invention comprises at least one battery cell comprising an anode, a cathode as defined above, a separator and an electrolytic solution based on a lithium salt and an organic solvent.
[0100] Electrolyte solution
[0101] As the electrolytic solution for lithium ion batteries, an organic electrolytic solution in which a supporting electrolyte is dissolved in an organic solvent can be used.
[0102] As supporting electrolyte, lithium salt can be used.Lithium salt is not particularly limited, and can use for example LiNO3, LiCl, LiBr, LiI, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, lithium chloroborate, lithium tetraphenylborate etc.Among these, preferred LiPF6, LiClO4, CF3SO3Li, because they are easily dissolved in organic solvents and show high dissociation degree.Two or more thereof can be used together.If the dissociation degree that supporting electrolyte has is higher, lithium ion conductivity is higher, so lithium ion conductivity can be adjusted by the type of supporting electrolyte.
[0103] The organic solvent for the electrolytic solution of the lithium ion battery is not particularly limited as long as the supporting electrolyte can be dissolved. Carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC) or methyl ethyl carbonate (MEC) can be used; esters such as γ-butyrolactone or methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as tetrahydrothiophene sulfone and dimethyl sulfoxide. Mixed solvents thereof can also be used. Among these, carbonates are preferred because they have a high dielectric constant and a wide stable potential. The lower the viscosity of the solvent used, the higher the lithium ion conductivity; therefore, the lithium ion conductivity can be adjusted by the type of solvent.
[0104] Further additives may be added to the electrolytic solution. Carbonates, such as ethylene carbonate (VC), are preferred as additives.
[0105] For the purpose of improving charge / discharge characteristics and flame retardancy, the electrolytic solution may contain at least one additive selected from the group consisting of pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, diethylene glycol dimethyl ether, benzene derivatives, sulfur, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole or 2-methoxyethanol.
[0106] The concentration of the supporting electrolyte in the electrolyte solution for lithium ion batteries is typically 0.01% to 30% by weight, preferably 0.05% to 20% by weight, particularly preferably 0.1% to 15% by weight, based on the total weight of the electrolyte solution. When the concentration of the supporting electrolyte is too low or too high, the ionic conductivity tends to decrease.
[0107] Diaphragm
[0108] As a separator for lithium ion batteries, known separators such as fine porous films or nonwoven fabrics can be used, which contain aromatic polyamide resins or polyolefin-based polymers such as polyethylene or polypropylene. For example, there can be mentioned a fine porous film formed by a resin such as a polyolefin-type polymer (polyethylene, polypropylene, polybutene, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-methacrylate copolymer and polyvinyl chloride) and a mixture or copolymer thereof; a fine porous film composed of an aggregate of polyethylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, polyaramid, polycycloolefin, nylon or polytetrafluoroethylene, a woven fabric (wherein a polyolefin-type fiber is woven) or a nonwoven fabric thereof and insulating material particles. The separator may also be composed of a porous substrate made of a mixture of inorganic particles and polymers; or the separator has a porous coating formed on at least one surface of a porous polymer substrate and contains inorganic particles and a binder polymer. Among these, a fine porous film formed of a polyolefin type polymer is preferred because the thickness of the separator as a whole can be made thinner and the capacity per volume can be increased by increasing the active material ratio in the battery.
[0109] The thickness of the separator is typically 0.01 to 300 μm, preferably 1 to 100 μm, and more preferably 1 to 40 μm. When the thickness is within this range, the resistance of the separator in the battery becomes smaller, and handling when forming a battery is superior.
[0110] In some cases, a gel polymer electrolyte may be coated on the separator to increase the stability of the battery cell. Representative examples of such gel polymers include polyethylene oxide, polyvinylidene fluoride, and polyacrylonitrile.
[0111] Anode (negative electrode)
[0112] The anode active material layer selectively includes a binder and a conductive agent in addition to the anode active material. The anode active material layer can be prepared by coating a composition for forming an anode on a negative electrode current collector (the composition selectively includes a binder and a conductive agent and an anode active material) and drying the coated anode current collector, or can be prepared by casting a composition for forming an anode on a separate support and then laminating a film separated from the support on the anode current collector. As the current collector, those mentioned in the lithium ion battery cathode can be mentioned, and as long as it is a material with conductivity and electrochemical durability, it is not particularly limited; however, copper is preferred as the anode of the lithium ion battery.
[0113] Anode active material
[0114] As the anode active material for the lithium ion battery anode, for example, carbon materials such as amorphous carbon, natural graphite, artificial graphite, natural black lead, medium carbon microbeads and pitch-based carbon fibers, conductive polymers such as polyphenylene or polyaniline can be mentioned. Moreover, as the anode active material, metals such as silicon, tin, zinc, manganese, iron and nickel, their alloys, oxides and sulfates of the above metals or alloys can be used. In addition, metals (including Si, Na, Al, Sn, Li, Zn, Mg, Cd, Ce, Ni and Fe), alloys of these metals; oxides of these metals such as LiCoO2, LiNiO2, LiMn2O4, MnO2, FeO2, V2O5, TiO2, Li x Ni 0,5 Mn 1.5 O4、Li x Mn 0,5 Ni 0,5 O2, metal hydroxides, metal sulfides such as LiVS2, LiTiS2, VS2 or TiS2, phosphates of these metals such as LiCoPO4, Li3V2PO4, LiTi2(PO4)3, LiFePO4, thiophosphates such as LiTi2(PS4)3, composites of the metals and carbon materials mentioned above; and mixtures thereof, lithium, lithium alloys such as LiC6, Li 13 Sn5, Li9Al4, Li 22 Si5 or lithium transition metal nitrides. As the anode active material, those having a conductive supply material attached to the surface by a surface mechanical modification method can also be used.
[0115] The content ratio of the anode active material of the anode active material layer is preferably 85% to 99.9% by weight based on the total weight of the anode active material layer, and more preferably 90% to 99.75% by weight. If a metal such as Si, Na, Al, Sn, Li, Zn, Mg, Cd, Ce, Ni or Fe is used for the anode active material, the content can reach 100%. By making the content ratio of the anode active material within the range, it can show flexibility and bonding characteristics while showing high capacity.
[0116] In addition, in the anode of the lithium ion battery, in addition to the above-mentioned components, a solvent used in the cathode of the above components or an electrolytic solution additive having a function of inhibiting decomposition of the electrolytic solution may be contained. These may not be particularly limited as long as they do not affect the battery reaction.
[0117] Anode Binder
[0118] As a binder for anodes of lithium ion batteries, known materials can be used without any particular restrictions. Examples of such binders for lithium ion batteries include polyethylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polyacrylic acid, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, lignin, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, polyamide-imide, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber derivatives or polyacrylonitrile derivatives; soft polymers, such as acrylic acid-based soft polymers. These can be used alone or by combining two or more thereof.
[0119] Negative electrodes for lithium-ion batteries can be produced in the same way as the positive electrodes described above.
[0120] Method for producing lithium-ion batteries
[0121] As a specific production method of lithium-ion batteries, the cathode and anode mentioned above can be layered by a diaphragm, and then wound or bent according to the shape of the battery to be assembled in a battery box, after which the electrolyte is injected into the battery box and the box is sealed. In addition, as required, the pressure inside the battery can be prevented from rising and overcharging-overdischarging by arranging overcurrent protection elements (such as fuses and PTC elements) and lead plates in expanded metals (such as sponge nickel). The shape of the battery can include a coin shape, a button shape, a plate shape, a cylindrical shape, a square shape, and a flat shape.
[0122] The invention is illustrated by the following non-limiting examples.
[0123] The following materials were used:
[0124]
[0125]
[0126]
[0127]
[0128] Test Method
[0129] Acrylonitrile content
[0130] The nitrogen content for determining the acrylonitrile content is determined in the nitrile rubber (1) by the Kjeldahl nitrogen method to DIN 53 625.
[0131] Mooney viscosity
[0132] The values for Mooney viscosity (ML 1+4@100° C.) were in each case determined at 100° C. by shear disk viscometer in accordance with DIN 53523 / 3 or ASTM D 1646. The MSR (Mooney stress relaxation) was in each case determined at 100° C. by shear disk viscometer in accordance with ISO 289-4:2003(E).
[0133] Particle size determination
[0134] The particle size of the powdered samples was determined using a laser diffuser. The samples were prepared using the Fraunhofer approximation, which calculates and determines the particle size distribution for a refractive index and an absorption index of "1". The volume histogram yields the D90 as a result of the analysis. The D90 describes the diameter at which ninety percent of the distribution has a smaller particle size and ten percent has a larger particle size.
[0135] Sticking trend
[0136] The sticking tendency of the powders was assessed visually and rated using the following criteria:
[0137] 1 = Sample does not stick and is free flowing
[0138] 2 = Sample exhibits only slight adhesion and falls apart under low pressure
[0139] 3 = Samples exhibit slight adhesion, stick together, and can be separated with gentle pressure
[0140] 4 = The sample undergoes strong adhesion and can only be separated by applying force, and the fragments continue to stick together 5 = The sample can no longer be separated into powder-like particles.
[0141] Solubility
[0142] These samples were dissolved according to the following procedure and their solubility was evaluated using the subsequent standards.
[0143] A 1 wt% sample was placed in a given solvent and shaken at 150 rpm at room temperature using an IKA shaker KS 4000i control model. After a given time, the sample was visually evaluated.
[0144] A = Sample not dissolved
[0145] B = Sample begins to dissolve, particles swell and most of the sample remains undissolved
[0146] C = Sample begins to dissolve, particles remain undissolved
[0147] D = Most of the sample is dissolved, with a small amount of residue or partial turbidity
[0148] E = Sample completely dissolved and showed no residue
[0149] NMR
[0150] The microstructure and termonomer content of these individual polymers were determined by 1H NMR (instrument: Bruker DPX400 with XWIN-NMR 3.1 software, measuring frequency of 400 MHz, solvent CDCl 3 ).
[0151] Method for evaluating peel strength
[0152] The evaluation of peel strength was carried out according to ASTM D903. The cathode plate was cut into test strips with a width of 25 mm and a length of 175 mm. 3M vinyl electrical tape was bonded to the coated cathode active material surface of the cathode plate. The test strips were subjected to peeling tests by an Instron tensile machine in a 180° direction at 100 mm / min peeling tape. The peeling force was recorded during the test. The peel strength was calculated according to the following formula:
[0153]
[0154] The average peel strength was calculated based on the 50-200 mm displacement data, and the average of three measurements was taken as the peel strength value.
[0155] Method for evaluating specific discharge capacity
[0156] The produced secondary battery was charged at 0.2C rate at 23°C until the battery voltage reached 4.2V. Subsequently, after 20 minutes, constant current discharge was performed at 0.2C rate at 23°C until the battery voltage reached 2.75V. Thereafter, the secondary battery of the button cell unit was charged and discharged in constant current mode (CC mode 0.2C rate). Between each cycle, the battery cell rested for 5min. The discharge specific capacity of the secondary battery was calculated as the average value between the 2nd and 5th cycles.
[0157] Method for evaluating capacity retention
[0158] The secondary battery of the button cell unit was charged and discharged for 30 cycles in constant current mode (CC mode 0.2C rate). The capacity retention rate was determined as the ratio of the discharge specific capacity after 30 cycles to the discharge specific capacity after the second cycle, expressed as a percentage.
[0159] Preparation of fully hydrogenated acrylonitrile butadiene terpolymer C containing acetoacetoxyalkyl methacrylate
[0160] The following materials were used as provided:
[0161] The monomer units acrylonitrile and acetoacetoxyethyl methacrylate were from Sigma-Aldrich, and 1,3-butadiene was from INEOS.
[0162] Solution Fe(II)SO4: Premixed solution contains 0.986g Fe(II)SO4*7H2O and 2.0g C.
[0163] EDTA: used as complexing agent, from Sigma-Aldrich.
[0164] Fatty acid: CAS 67701-08-8, emulsifier for polymerization.
[0165] Abietic acid: disproportionated abietic acid, sodium salt, CAS 61790-51-0.
[0166] t-DDM: Molecular weight regulator from Arlanxeo Deutschland GmbH.
[0167] From Akzo-Degussa NT50, p-Menthane hydroperoxide. Initiator for emulsion polymerization.
[0168] Diethylhydroxylamine: polymerization terminator, CAS 3710-84-7.
[0169] Antioxidants: 1520-2-Methyl-4,6-bis(octylthiomethyl)phenol (BASF AG, Germany), 1076-octadecyl-β-(4-hydroxy-3,5-di-tert-butyl-phenyl)-propionate (BASF GmbH, Germany) and A mixture of equal amounts of L-poly(dicyclopentadiene-co-p-cresol) (Omnova, Italy).
[0170] Dry monochlorobenzene (MCB) from VWR Corporation.
[0171] Wilkinson catalyst from Materia Inc. and triphenylphosphine from VWR were used as hydrogenation catalysts.
[0172] The acetoacetoxyalkyl-containing fully hydrogenated acrylonitrile butadiene terpolymer C used as the base polymer for preparing the powdered rubber in the following series of examples was produced according to the following description, wherein all raw materials are expressed in parts by weight based on 100 parts by weight of the monomer mixture in Table 1.
[0173] Acrylonitrile butadiene terpolymer C was produced in batches in a 5 L autoclave with a stirrer system. In the autoclave batch, 1.25 kg of monomer mixture and 2.1 kg total amount of water, and EDTA in an equimolar amount based on Fe(II) were used. Initially, 1.9 kg of this amount of water and emulsifier were loaded into the autoclave and purged with a nitrogen stream. Thereafter, destabilizing monomers and t-DDM (tert-dodecyl mercaptan) as a molecular weight regulator were added and the reactor was closed. After heating the reactor contents, the mixture was stirred by adding a premixed solution of Fe(II)SO4 and p-menthane hydroperoxide ( NT50) was used to start the polymerization. The polymerization process was monitored by gravimetric determination of the conversion. When the conversion reported in Table 1 was reached, the polymerization was stopped by adding an aqueous solution of diethylhydroxylamine. Unconverted monomers and other volatile components were removed by steam distillation.
[0174] A 50% dispersion of the antioxidant was mixed with the acrylonitrile butadiene terpolymer dispersion and its solid content was adjusted to 17.5% by weight. Subsequently, the resulting dispersion comprising the acrylonitrile butadiene terpolymer containing acetoacetoxyalkyl groups and the antioxidant was slowly added to an aqueous calcium chloride solution having a concentration of 0.34% by weight at 60° C. at a constant pH of 6 with vigorous stirring. The stabilized coagulated terpolymer was washed with water at pH 6 and a temperature of 60° C. and dried in a vacuum oven for 16 hours.
[0175] After hydrogenation with a standard Ru-based hydrogenation catalyst in chlorobenzene according to Table 1, the hydrogenated acrylonitrile butadiene terpolymer C containing acetoacetoxyalkyl groups obtained has the characteristics reported in Table 2. The spectrum of the acrylonitrile butadiene rubber terpolymer containing acetoacetoxyalkyl ester groups before, during and after the hydrogenation reaction was recorded on a Perkin Elmer spectrum 100 FT-IR spectrometer. The solution of the acrylonitrile butadiene rubber terpolymer in chlorobenzene was cast onto a KBr disk and dried to form a film for testing. The hydrogenation conversion was determined by FT-IR analysis according to ASTM D 5670-95 method.
[0176] Table 1: Preparation of Hydrogenated Acrylonitrile-Butadiene Rubber Copolymer C Containing Acetoacetoxy Alkyl Groups
[0177]
[0178] 1) Premix solution contains 0.986 g Fe(II)SO4*7H2O and 2.0 g C
[0179] Table 2: The monomer unit content, residual double bond % and Mooney viscosity of polymer C prepared according to Table 1
[0180]
[0181] Preparation of powdered rubber
[0182] The rubber is mixed intimately with the amount of separating agent specified in each case in a beaker and added gradually to the ZM 200 ultracentrifugal mill. The mill was equipped with an annular screen with an average mesh size of 0.25 mm and was operated at a speed of 10 000 rpm. During grinding, the mill was cooled with liquid nitrogen. After grinding, the powder was removed from the grinding chamber by a cyclone separator and collected. All the obtained powders were dried at 55° C. for 24 h. The obtained powders were evaluated.
[0183] The powder mixture according to the present invention using lithium stearate as a separator has an average particle size D(90) preferably in the range of 0.05 mm to 3 mm, more preferably in the range of 0.08 mm to 2 mm, in particular in the range of 0.10 mm to 1.75 mm and particularly preferably in the range of 0.10 mm to 1.5 mm.
[0184] The results of the prepared inventive polymer powders and comparative polymer powders are shown in Tables 3-6.
[0185] Table 3: Composition and properties of innovative polymer powders 1-6
[0186]
[0187] Table 4: Composition and properties of innovative polymer powder 7-11
[0188]
[0189] Table 5: Composition and properties of comparative polymer powders 12-17 using alternative release agents
[0190]
[0191] np*: Unable to measure due to sample adhesion
[0192] Table 5:Composition and properties of comparative polymer powders 18-23 using alternative release agents
[0193]
[0194]
[0195] np*: Unable to measure due to sample adhesion
[0196] Table 6: Composition and properties of comparative polymer powders 24-29 using alternative release agents
[0197]
[0198] np*: cannot be measured due to sample adhesion; ** solid pieces of rubber that cannot be separated into powdery particles
[0199] Table 7: Comparison of the composition and properties of polymers 30-32
[0200]
[0201] **Solid pieces of rubber that cannot be separated into powdery particles
[0202] It can be noted that when lithium stearate is used as a dust suppressant, free-flowing powders can be easily obtained. This is true for several types of elastomers. Sample 16 ( 900, with silica as dust suppressant) requires more than sample 1 ( 900, with lithium stearate) a greater amount of dust suppressant and indeed even resulted in a powder with a larger particle size than the innovative powder. The same is true when XT is used as the base polymer, even with less dust suppressant, a smaller powder size can be obtained.
[0203] Different powdered samples of the invention and the corresponding base polymer were dissolved in NMP and their solubility was evaluated after 90 min. It can be noted that all powdered samples of the invention dissolved faster than the base polymer, resulting in an increased cell productivity of the battery.
[0204] Table 8: Comparative solubility test of polymers 25, 26, 28, 29, 31, and 32
[0205]
[0206] Table 9: Solubility test of polymer powders 1, 2, 4, 5, 10, and 11 of the present invention
[0207]
[0208] General method for manufacturing button cell battery
[0209] Step (1) - Dissolution : A certain amount of polymer was dissolved in a solvent (NMP) in an oscillator at room temperature overnight to form a binder solution (5 wt.-%).
[0210] Step (2) - Preparation of cathode slurry composition : The binder solution from step 1 was mixed with the active material (NMC111) and the conductive material (conductive carbon black Super P) in a planetary ball mill (ball milling conditions: 28 Hz, 6 minutes, room temperature) to obtain a cathode slurry composition.
[0211]
[0212] Weight ratio: NMC / polymer / NMP / Super P = 80 / 10 / 190 / 10 (polymer concentration in NMP = 5 wt.-%)
[0213] Step (3) - Production of cathode disk : The cathode slurry composition was applied to a current collector (aluminum foil) using a bar coater at a coating speed of 2.8 mm / s to form a cathode plate. The coater slit gap of the coater was adjusted to 150 μm to obtain a predetermined coating thickness.
[0214] Step (4) - Drying The cathode plate was dried in an oven at 80°C for 120 minutes to remove NMP and moisture. After drying, the cathode plate was calendered to adjust the surface density (weight: 12-19 mg / plate; plate area: 201 mm 2 ; Density: 60-95g / m 2 From the rolled cathode plate, a cathode disk ( 16mm) for punching. The punch edge is sharp without burrs.
[0215] Step (5) - Assembly of lithium-ion secondary battery:Assembly and pressing of lithium-ion secondary batteries are performed in a glove box. The assembly includes the top of the button cell housing (2032 type; negative electrode), sponge nickel, lithium disk (as anode), porous separator (Celgard 2340), cathode disk and housing bottom (positive electrode). All parts are assembled layer by layer. Electrolytic solution is dripped during the assembly step to completely fill the free volume of the button cell. Finally, the button cell box is pressed by a press in the glove box. An open circuit voltage test is performed to check whether a short circuit occurs.
[0216] Table 10 : Determination of the peel strength of the cathode plates of lithium ion battery comparative examples 1 to 3 and example 4 of the present invention
[0217]
[0218] Compared to Comparative Example 3 using PVDF as the cathode binder, Inventive Example 4 showed higher peel strength. Using a powdered polymer as the cathode binder resulted in an electrode plate with a peel strength still high compared to Comparative Examples 1 and 2.
[0219] Table 11 : Determination of the discharge specific capacity and capacity retention rate of lithium ion battery comparative examples 1-2 and example 4 of the present invention
[0220]
[0221] The results in Tables 10-11 show that using free-flowing powdered rubber with lithium stearate as a binder for batteries results in higher capacity retention than using base polymers or polymer powders with different types of dust suppressants. They can also dissolve faster than base polymers, which is beneficial for battery cell production.
[0222] It should be understood that the various aspects and embodiments of the specific embodiments as disclosed herein are illustrations of specific ways to make and use the invention and do not limit the scope of the invention when considering the claims and the specific embodiments. It should also be understood that features from different aspects and embodiments of the invention can be combined with features from different aspects and embodiments of the invention.
Claims
1. An elastomer powder mixture comprising (1)(a) An ethylene-vinyl acetate copolymer comprising the following repeating units: - ethylene monomer, and - vinyl acetate monomer in an amount of at least 70% by weight and based on the total weight of the ethylene-vinyl acetate copolymer; or (b) a nitrile rubber copolymer, which is optionally carboxylated and contains the following repeating units: - α,β-unsaturated nitrile monomers selected from the group consisting of acrylonitrile, methacrylonitrile, ethacrylonitrile and mixtures thereof, in each case in an amount of at least 15% by weight and based on the total weight of the nitrile rubber copolymer, and - a conjugated diene monomer, which is optionally fully or partially hydrogenated and is selected from the group consisting of 1,2-butadiene, 1,3-butadiene, isoprene, 2,3-dimethylbutadiene, piperylene and mixtures thereof; as well as (2) A dust suppressant comprising lithium stearate.
2. The powdery mixture according to claim 1, having a particle size distribution D90 of at least 100 μm as determined by using a laser diffuser.
3. The powdery mixture according to any one of claims 1 to 2, wherein The nitrile rubber copolymer (b) is a carboxylated nitrile rubber (XNBR) which is optionally fully or partially hydrogenated.
4. The powdery mixture according to any one of claims 1 to 4, wherein The ethylene vinyl acetate copolymer (a) and / or the nitrile rubber copolymer (b) has a Mooney viscosity (ML (1+4) 100° C.) of ≥ 25 Mooney units (MU) at 100° C., measured by shear disc viscometer according to DIN 53523 / 3 or ASTM D 1646.
5. The powdery mixture according to any one of claims 1 to 4, which additionally comprises an epoxy-containing fluorine-free copolymer comprising repeating units derived from one or more epoxy-containing monomers of the general formula (I): in m is 0 or 1, and X is O, O(CR2) p , (CR2) p O, C(=O)O, C(=O)O(CR2) p , C(=O)NR, (CR2) p 、N(R)、N(R)(CR2) p 、P(R)、P(R)(CR2) p ,P(=O)(R),P(=O)(R)(CR2) p , S, S (CR2) p 、S(=O)、S(=O)(CR2) p 、S(=O)2(CR2) p or S(=O)2, wherein R in these groups may have 1 -R 6 The same definition, Y represents a repeating unit derived from one or more monounsaturated or polyunsaturated monomers including conjugated or non-conjugated dienes, alkynes and vinyl compounds, or a structural element derived from a polymer including polyethers, more particularly polyalkylene glycol ethers and polyoxyalkylenes, polysiloxanes, polyols, polycarbonates, polyurethanes, polyisocyanates, polysaccharides, polyesters and polyamides, n and p are identical or different and are each in the range of 0 to 10 000, R, R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are identical or different and are H, a linear or branched saturated or monounsaturated or polyunsaturated alkyl group, a saturated or monounsaturated or polyunsaturated carbocyclyl or heterocyclyl group, an aryl, heteroaryl, aralkyl, heteroaralkyl, alkoxy, aryloxy, heteroaryloxy, amino, amido, carbamoyl, alkylthio, arylthio, sulfanyl, thiocarboxy, sulfinyl, sulfo, sulfinyl, sulfoxy, sulfonic acid, sulfamoyl, hydroxyimino, alkoxycarbonyl, F, Cl, Br, I, hydroxy, phosphonate, phosphinate, silyl, siloxy, nitrile, borate, selenate, carbonyl, carboxyl, oxycarbonyl, oxysulfonyl, oxo, thio, epoxy, cyanate, thiocyanate, isocyanate, thioisocyanate or isocyanide.
6. A cathode slurry composition comprising - a powdery mixture according to any one of claims 1 to 5, - at least one cathode active material, - at least one electrically conductive material, and - at least one solvent.
7. The cathode slurry composition according to claim 6, wherein The at least one cathode active material comprises a compound having the following Formula 1: Li 1+a Ni x Co y Mn z M w O2 [Formula 1] Among them, M can be at least one selected from the group consisting of: aluminum (Al), copper (Cu), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), zirconium (Zr), zinc (Zn), tantalum (Ta), niobium (Nb), magnesium (Mg), boron (B), tungsten (W), and molybdenum (Mo), and a, x, y, z, and w represent the atomic fractions of each independent element, where -0.5 ≤ a ≤ 0.5, 0 < x ≤ 1, 0 < y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ w ≤ 1, and 0 < x + y + z ≤ 1; or lithium iron phosphate (LFP).
8. The cathode slurry composition according to claim 6 or 7, wherein The at least one conductive material is selected from the group consisting of: carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and summer black, natural and artificial graphite, expanded graphite, conductive fibers such as carbon fibers and metal fibers, metal powders such as carbon fluoride, aluminum powder, and nickel powder, and carbon nanotubes, graphene, graphene oxide, and mixtures thereof.
9. The cathode slurry composition according to any one of claims 6 to 8, wherein The at least one conductive material is present in an amount of 0.5% to 50% by weight based on the total solid weight of the cathode paste composition.
10. The cathode slurry composition according to any one of claims 6 to 9, wherein The at least one solvent includes cycloaliphatic hydrocarbons, aromatic hydrocarbons, ketones, chloroaliphatic hydrocarbons, esters, acrylonitrile, ethers, alcohols, nitriles, or amides, preferably methyl ethyl ketone, toluene, and / or N-methylpyrrolidone.
11. A cathode, which includes a current collector and a cathode active material layer, wherein the cathode active material layer contains the powdery mixture and the conductive material according to any one of claims 1 to 5.
12. The cathode according to claim 11, wherein The current collector is selected from the group consisting of: iron, copper, aluminum, nickel, sintered carbon, stainless steel, stainless steel treated with carbon, titanium, tantalum, gold, platinum, titanium, or silver on its surface; aluminum cadmium alloy, non-conductive polymer treated with a conductive material on its surface; conductive polymer, or a metal paste containing metal powders of Ni, Al, Au, Ag, Pd, Cr, Ta, Cu, or Ba.
13. A lithium-ion battery, which includes at least one battery cell, and the at least one battery cell includes an anode, the cathode according to claim 11 or 12, a separator, and an electrolytic solution based on a lithium salt and an organic solvent.
14. Use of the powdery mixture according to any one of claims 1 to 5 as a binder in an electrode composition for a cathode of a battery cell for a battery.
Citation Information
Patent Citations
Pulverulent mixtures containing low-emission nitrile rubbers
EP3283538A1
Electrode composition for a cathode of a cell of a lithium-ion battery, a cathode slurry composition, a cathode and the battery incorporating it
EP3900086A1
Pulverulent mixture of precrosslinked nitrile rubbers
EP3902855A1